2004
DOI: 10.1097/00042737-200401000-00004
|View full text |Cite
|
Sign up to set email alerts
|

p14ARF gene alterations in human hepatocellular carcinoma

Abstract: We can conclude that p14(ARF) is frequently and early altered in HCC, being the main cause of inactivation promoter hypermethylation. Our results suggest that the p14(ARF) gene plays an important role in the pathogenesis of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…The presence of p14 methylation could be attributed to that P14 was reported to be preferentially methylated in HCV related HCC (Yang et al, 2003). Matching with our results, Anzola et al reported the methylation frequency of p14 in 41.9% out of 117 HCC cases (Anzola et al, 2004). Also, Liu et al (2006) reported the frequency of p14 methylation in 36% out of 50 HCC cases (Liu et al, 2006) but they did not include normal controls in their comparison as we did.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of p14 methylation could be attributed to that P14 was reported to be preferentially methylated in HCV related HCC (Yang et al, 2003). Matching with our results, Anzola et al reported the methylation frequency of p14 in 41.9% out of 117 HCC cases (Anzola et al, 2004). Also, Liu et al (2006) reported the frequency of p14 methylation in 36% out of 50 HCC cases (Liu et al, 2006) but they did not include normal controls in their comparison as we did.…”
Section: Discussionsupporting
confidence: 90%
“…2 Recent advances in molecular genetics indicate that activation of oncogenes or inactivation of tumor suppressor genes might have an important role in HCC tumorigenesis. 3,4 Many studies demonstrated that abnormal changes in DNA methylation (including methylation content, level, and pattern) lead to the inactivation of some tumor suppressor genes, such as p16, p15, p14ARF, and RASSF, [5][6][7][8] which are involved in HCC carcinogenesis. These changes usually occur in 5'-CpG (5'-CG-3' palindrome; p, phosphate group) dinucleotides that are clustered frequently in regions approximately 1 to 2 kb long, called 5'-CpG islands, in or near the promoter and the first exon region of genes.…”
Section: Introductionmentioning
confidence: 99%
“…Although FoxM1 is over-expressed in HCC, the extent to which Arf is mutated or silenced in HCC is not clear. One study with 117 HCC samples provided evidence for loss of Arf expression by hypermethylation in about 42% of the samples and loss of heterozygosity in 27% of the samples (27). Also, it is possible that high-level expression of FoxM1 is able to overcome the Arf-regulation and induce development of aggressive HCC.…”
mentioning
confidence: 99%